Bacterial Response to Oxidative Stress and RNA Oxidation - Seixas, André F.; Quendera, Ana P.; Sousa, João P.; Silva, Alda F. Q.; Arraiano, Cecília M.; Andrade, José M. (Frontiers in Genetics, 2022)
Bacteria have to cope with oxidative stress caused by distinct Reactive Oxygen Species (ROS), derived not only from normal aerobic metabolism but also from oxidants present in their environments. The major ROS include superoxide O2-, hydrogen peroxide H2O2 and radical hydroxide HO•. To protect cells under oxidative stress, bacteria induce the expression of several genes, namely the SoxRS, OxyR and PerR regulons. Cells are able to tolerate a certain number of free radicals, but high levels of ROS result in the oxidation of several biomolecules. Strikingly, RNA is particularly susceptible to this common chemical damage. Oxidation of RNA causes the formation of strand breaks, elimination of bases or insertion of mutagenic lesions in the nucleobases. The most common modification is 8-hydroxyguanosine (8-oxo-G), an oxidized form of guanosine. The structure and function of virtually all RNA species (mRNA, rRNA, tRNA, sRNA) can be affected by RNA oxidation, leading to translational defects with harmful consequences for cell survival. However, bacteria have evolved RNA quality control pathways to eliminate oxidized RNA, involving RNA-binding proteins like the members of the MutT/Nudix family and the ribonuclease PNPase. Here we summarize the current knowledge on the bacterial stress response to RNA oxidation, namely we present the different ROS responsible for this chemical damage and describe the main strategies employed by bacteria to fight oxidative stress and control RNA damage.